Sectioned Faraday Cylinder for Magnetized High-Current Beams; Instruments and Experimental Techniques; Vol. 23, № 2 - Gleizer I. Z.; Usov Y. P. Yuri Petrovich; Tsvetkov V. I.; Shatanov A. A. (1980, 1980)
The construction and the results of tests of a sectioned 21-channel Faraday cylinder for pulsed, high-current, magnetized beams are described. The sensitivity of each of the channels can be regulated separately using a special mask. The instrument is designed to measure the current density distribution in a high-current electron beam formed in a diode with magnetic insulation. The results of measurements of the current density in the tubular beam of the Tonus-2M high-current accelerator are presented.